2021
DOI: 10.48550/arxiv.2110.03957
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bounds for the Twin-width of Graphs

Jungho Ahn,
Kevin Hendrey,
Donggyu Kim
et al.

Abstract: Bonnet, Kim, Thomassé, and Watrigant [8] introduced the twinwidth of a graph. We show that the twin-width of an n-vertex graph is less than pn `?n ln n `?n `2 ln nq{2, and the twin-width of an m-edge graph is less than ? 3m `m1{4 ? ln m{p4 ¨31{4 q `3m 1{4 {2. Conference graphs of order n (when such graphs exist) have twinwidth at least pn ´1q{2, and we show that Paley graphs achieve this lower bound. We also show that the twin-width of the Erdős-Rényi random graph Gpn, pq with 1{n ď p " ppnq ď 1{2 is larger t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Often, graph families where a certain width parameter is bounded possess favorable structural, algorithmic, or combinatorial properties. The powerful twin-width parameter, introduced recently in [15], generalizes treewidth and clique-width and has attracted a lot of recent attention [1,8,25,50,51]. Graph families of bounded twin-width are positive examples to the IGQ [14], making them a natural choice for studying Question 1.2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Often, graph families where a certain width parameter is bounded possess favorable structural, algorithmic, or combinatorial properties. The powerful twin-width parameter, introduced recently in [15], generalizes treewidth and clique-width and has attracted a lot of recent attention [1,8,25,50,51]. Graph families of bounded twin-width are positive examples to the IGQ [14], making them a natural choice for studying Question 1.2.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that this would have an unintuitive consequence for communication complexity: computing adjacency in graphs from a hereditary, factorial family would have complexity 𝑂 (1) or Ω(log log 𝑛) but nothing in between; see Example 1.13. This is similar to the jump between 𝑂 (1)-size and Ω(log 𝑛)-size deterministic adjacency labeling schemes, and the jumps in the speed of hereditary graph families, so it seemed reasonable to expect a similar jump for communication.…”
Section: Discussion and Subsequentmentioning
confidence: 99%
See 3 more Smart Citations